Synthesis of PES and PES/chitosan membranes for synthetic acid mine drainage treatment - Mathaba J Machodi; Michael O Daramola (Water SA, 2020)
In this study, chitosan was synthesised from chitin and used to modify polyethersulphone (PES) membrane prepared by the phase inversion method. PES membrane was blended with various concentrations of chitosan to produce PES/0.5 wt% chitosan, PES/0.75 wt% chitosan and PES/1 wt% chitosan membranes. The membranes were tested for metal and sulphate removal from acid mine drainage (AMD). The fabricated membranes were characterised using scanning electron microscopy (SEM), contact angle analyser, Fourier transform infrared (FTIR), porosity determination and pure water flux measurements. Separation performance was conducted on a dead-end filtration cell and metal ions were determined by atomic absorption spectroscopy (AAS), and ultraviolet and visible (UV-vis) spectrophotometry was used for sulphates. Pure water flux of the pristine PES membrane increased from 102 L∙m−2∙h−1 to 107 L∙m−2∙h−1 and 133 L∙m−2∙h−1 for PES/0.5 wt% and PES/0.75 wt%, respectively. Further addition of chitosan to 1 wt% created a dense structure on the membrane surface, thereby reducing the flux to 120 L∙m−2∙h−1. The rejection of cations and sulphate ions significantly improved for chitosan-modified membranes due to the creation of adsorptive and/or repulsive sites on the chitosan biopolymer as a result of amine group protonation. The results reveal that chitosan has potential to improve performance of PES membranes as a hydrophilic agent during AMD treatment.